Adsorbsi gas karbon dioksida dalam biogas dengan menggunakan endapan batu kapur - Sutanto, R.; Mulyanto, A.; Wirawan, M.; Alit, I.B.; Nurchayati, N. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2019)
With the depleting reserves of energy sources and fuel shortages that occur in Indonesia today, it is needed a cheap alternative energy sources and environmentally friendly, one of which is biogas. In this study biogas is generated from horse manure. The fermentation of horse manure can produce biogas with the largest component of the CH4 (49.5%) and CO2 (49.7%). The use of biogas as a fuel is still in the household scale and has not been used optimally. This is due to the biogas still containing high levels of CO2 so that it has low value of heat is produced. This research reduces the CO2 levels by using the Ca(OH)2 or limestone sedimentary, and then react with the CO2 to form CaCO3 and H2O. The variables  studied are the influence of the flow rate of the biogas that CO2 absorbed and CH4. CO2 absorption made by passing the biogas with a variety of flow rates in the Ca(OH)2 at a certain concentration. Gas and Ca(OH)2 contact each other and the chemical reaction occurs. Every 2 minute interval of gas coming out of the absorber is detected by a biogas tester for analysis of absorbed CO2 and CH4 produced. The research results show that the average CO2 can be absorbed at all the variations of biogas flow rate (5 liter/min. 10 liter/min and 15 liter/min) produced CH4 at the biogas flow rate of 10 liter/min is 91%, then at the flow rate of 5 liter/min is 76.2% and at the flow rate of 15 liter/min is 72%.